Why America's top pundits are wrong - "Besteman, Catherine" (Berkeley, 2005)
This book confronts some of the most controversial and divisive issues of the day. Why does poverty persist in the United States? Do the poor, through or lack of initiative, somehow deserve their plight? Why do African Americans continue to get left behind in the American race for sucoma? Are feminists right about violence against women in our society? How much of our behavior is genetically programmed? Why do some countries do better than others in the global economy? Why has the US military found itself fighting Muslims so much of late? Will global ization and US intervention abroad create a more peaceful or a more polarized world? Should the United States have intervened in the former Yugoslavia in the 1990s, or is that part of the world doomed to bloody and irremediable ancient hatreds?
Keywords: Mass media and anthropology